(untitled) (PERcursos Linguísticos, 2025)
This article aims to investigate the construction of the notion of femininity of the character Jules from the series Euphoria, based on Bakhtin’s (2011) postulates about alterity. We start from the representation of LGBTQIAPN+ subjects presents in media services and how they construct and perceive their own bodies in the development of their narratives. We will carry out a qualitative and interpretative research approach, having as a method of analysis the methodological contributions of the verbivocovisuality (Paula and Luciano, 2020), applied to the episodes: Shook One, Pt. II and Fuck Anyone Who’s Not a Sea Blob – Part 2: Jules. We realize that Jules, initially, links her femininity to the desires of the people she lives with and it is only through her personal maturity that she begins to build her femininity based on her own tastes, without overlooking the interference of others in this process of construction.